Amor feminino: do desamparo à devastação - Passos, Carina Freitas (2017)
This dissertation aims to analyze the female subject that sustains psychically in the violent bond. Countersigned in this scenario emerges the problematic that sustains the question "Why it does not just go away?", That it touches the movement of women in the face of situations of violence. Starting from this bias, the character "O" of Pauline Réage (1954/1972), in the work The history of O. This character corroborates with the premise of this research that there is an intrinsic relation Between the constitution of the female subject, masochism and fundamental helplessness when presenting herself as a woman who yields to the lover's wishes, without refusals. It was necessary to go through the theoretical constructions of Freud and Lacan, following contemporary theorists, to elucidate the concepts of helplessness, and its nuances, and masochism, in their articulations with the process of subjectivation. In fact, it was necessary to address the specificities of the female Oedipus complex to question about the choice of object and partner devastation. Devastation emerges as a peculiar form of the female subject, especially in the loving partnership in which there is self-giving, which refers to the way of relating to the primordial Other. This shows the incessant demand of love to the Other, notoriously related to the devastation. On this point one can analyze that the character "O", when submitting to his lovers without limit to the concessions that he makes of his body (in a relation of total servitude) is cherished by the words of love said to her. The research allowed to understand the constitution of the female subject in this relation of servitude to the Other. In this scenario, female masochism arises in the face of the impossibility of supporting the helplessness, which finds a fatal destiny, making possible the exit by the devastation.